Robust Adaptive Fuzzy Output Tracking Control for a Class of Twin-Roll Strip Casting Systems. (5th June 2017) - Zhang, Yu-Jun; Wu, Li-Bing; Zhao, Hong-Yang; Hu, Xiao-Dong; Zhang, Wen-Yu; Ju, Dong-Ying
Abstract : This paper is concerned with the adaptive fuzzy control problem for a class of twin-roll strip casting systems. By using fuzzy logic systems (FLSs) to approximate the compounded nonlinear functions, a novel robust output tracking controller with adaptation laws is designed based on the high gain observer. First, the nonlinear dynamic equations for the roll gap and the molten steel level are constructed, respectively. Then, the mean value theorem is employed to transform the nonaffine nonlinear systems to the corresponding affine nonlinear systems. Moreover, it is also proved that all the closed-loop signals are bounded and the systems output tracking errors can converge to the desired neighborhoods of the origin via the Lyapunov stability analysis. Finally, simulation results, based on semiexperimental system dynamic model and parameters, are worked out to show the effectiveness of the proposed adaptive fuzzy design method.